Triggers and Barriers of Public Innovation: Perceptions from the Network of Public Innovators in Chile - Cienfuegos, Ignacio; Vera, Angélica (Revista del CLAD Reforma y Democracia, 2019)
This article assumes the existence of a limited theoretical production, as well as few empirical studies on innovation in the public sector. Nevertheless, there would be some approaches available for the study of innovation in State organizations. This research has focused specifically on the innovation process, that is, on the factors that would facilitate or hinder innovation in public organizations (Brown, 2010). In this way, the main barriers and triggers of innovation reported in the literature have been systematized, factors that have been transferred to a Likert scale, designing a survey that was then applied to the members of the Network of Public Innovators of Chile. This Network had 3,379 members at the time of the investigation, having obtained 425 responses from officials from different public institutions. This is how the presence of the key factors of innovation selected from the literature could be observed indirectly, collecting the perception of a sample of Chilean public officials, regarding the factors that influence the development or inhibition of innovation processes in their organizations. In addition to this empirical contribution, arguments from different lines of the specialized literature were identified, strengthening the relevance and validity of the selected factors, which included approaches from learning and organizational change, public management, neo-institutionalism, risk management among other theoretical approaches.